Photoionization excitation of the 2890-A Band - R. W. Carlson; D. L. Judge; M. Ogawa (Journal of Geophysical Research, 1973)
BACKGROUND: Colorectal cancer (CRC) is a leading cause of cancer-related morbidity and mortality. Physicians serve as role models for preventive care, yet data on CRC screening uptake among German visceral medicine specialists are scarce. METHODS: An anonymous, questionnaire-based cross-sectional survey was conducted among participants of the Visceral Medicine 2021 Congress in Leipzig. Physicians reported sociodemographics, personal colonoscopy participation and lifestyle factors. Descriptive and inferential analyses were performed. RESULTS: Of 369 physicians included, 54.4% had undergone a colonoscopy. Among those aged ≥ 50 years (n = 177), 81.9% had participated, three-quarters within the CRC screening program. Notably, 28.9% of physicians < 50 years had already undergone colonoscopy, mainly for screening purposes. Outpatient physicians were significantly more likely to have undergone colonoscopy, independent of age and sex. Medical specialty was not significantly associated with participation. CONCLUSIONS: Visceral medicine physicians show higher CRC screening participation than the general population. Lower participation among hospital-based physicians suggests structural disparities warranting further investigation.